Aramid micro-nano particles, preparation method and application thereof in aramid paper

The mixing and hot pressing of aramid micro-nano particles prepared by electrostatic spray, aramid short fiber and precipitated fibers, solve the problems of poor bonding effect and low density during the hot pressing process of existing aramid paper, and achieve the improvement of mechanical and electrical properties of aramid paper.

CN116971205BActive Publication Date: 2025-04-18ZHEJIANG SCI-TECH UNIV

Patent Information

Application Number
CN202311144831.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-04-18
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

During the hot pressing process of existing aramid paper, due to the poor compatibility of the precipitated fibers and the aramid short fibers obtained by wet spinning, the adhesion effect is poor, the paper-forming density is low, the pore structure remains, and the mechanical and electrical properties are poor.

Method used

Electrostatic spraying method is used to prepare aramid micro-nano particles and mixed them with aramid staple fibers and precipitated fibers. Through the hot pressing process, the aramid micro-nano particles are firmly bonded to adjacent fibers as "bridged" particles, improving interface abutment and paper-forming density.

Benefits of technology

By increasing the fluidity and filling properties of aramid micro-nano particles, the pores in aramid paper are minimized, and the mechanical strength and electrical properties are improved, so that the obtained aramid paper has high tensile strength, high breakdown voltage and high dielectric constant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116971205B_ABST
    Figure CN116971205B_ABST
Patent Text Reader

Abstract

The present invention discloses an aramid micro-nano particle, a preparation method and an application thereof in aramid paper. Monodisperse aramid micro-nano particles are prepared by using a polyisophthalamide (m-phenylene diamine) solution as a raw material and an electrostatic spraying method. When the aramid micro-nano particle is mixed with aramid short fibers and / or fibrils, the aramid micro-nano particle can fill the pores between the aramid short fibers and / or fibrils. Under the action of hot pressing, the particle melts and acts as a "bridging" particle to firmly bond adjacent aramid short fibers and / or fibrils, thereby improving the interfacial adhesion and cohesion, thereby giving the paper-based material excellent mechanical strength and electrical properties. The content and size of the aramid micro-nano particles are further controlled to obtain aramid paper with high tensile strength, high breakdown voltage and high dielectric constant. The mechanical and electrical properties of aramid fibers are fundamentally improved, so that the obtained aramid paper can be used in high-end applications while reducing the use of chemicals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to aromatic polyamide materials, and in particular to aramid micro-nano particles, a preparation method and application of the particles in aramid paper. Background Art

[0002] Insulation materials are the key to ensure the reliable, durable and safe operation of large-scale electrical insulation equipment, and directly affect the comprehensive quality, temperature resistance level and service life of electrical equipment. Aramid insulation paper (hereinafter referred to as aramid paper) is a high-performance paper-based material made from aramid fiber. Due to its excellent mechanical toughness, electrical insulation performance, thermal stability, flame retardancy and corrosion resistance, it is widely used as the main insulation material between turns, between phases, windings and wire ends of large-scale electrical equipment such as high-power dry-type transformers, oil-immersed transformers, special motors for mining, high-speed train traction motors, wind turbines, and ultra-high voltage transformers.

[0003] The main components of aramid paper are aramid staple fibers and fibrils. Among them, aramid staple fibers are crisscrossed and dispersed in the paper sheets to play a reinforcing role, making the finished paper have a higher tear strength; while fibrils play a role of filling short fibers and bonding in aramid paper. Its structure and performance are crucial to paper sheet formation and paper quality. At present, domestic aramid paper mostly uses aramid staple fibers obtained by wet spinning. The skin-core structure of aramid staple fibers obtained by wet spinning leads to complete surface hydrogen bonding and few oxygen-containing sites. During production, it was found that when the fibrils were bonded with the short fibers obtained by wet spinning under hot pressing, due to the lack of sites and the limited fluidity of the fibrils, they had poor compatibility with each other, and the resulting aramid paper had many problems: 1. The adhesion between the fibrils and the short fibers was poor, and the bonding effect was poor; 2. The finished paper had a low density and a large amount of pore structure remained; 3. The finished paper had poor mechanical and electrical properties, etc. In order to overcome the above problems, the current mainstream method is to further modify aramid paper by nanofibers. For example, Chinese patent (CN202010097567.0) discloses improving the performance of aramid paper by applying aramid nanofiber coating liquid, but this method is only for the surface of aramid paper and cannot improve the overall performance of aramid paper at a deeper level; Chinese patent (202210733407.X) discloses preparing aramid paper by adding nanofibers, and utilizing the full adhesion and interweaving of aramid nanofibers with the surface of aramid chopped fibers to further improve the tensile strength and tear strength of aramid fibers, thereby improving the mechanical properties and hardness of the resulting aramid paper. However, this method is limited by the length of aramid nanofibers and cannot further improve their fluidity and filling properties to obtain high-performance aramid paper.

[0004] Therefore, there is an urgent need to develop a material that can effectively fill the pores in aramid paper and play an adhesion role to solve the above problems. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention proposes an aramid micro-nano particle, a preparation method and its application in aramid paper. When it is used as a filling material in aramid paper, it exhibits excellent fluidity and filling properties, and the obtained aramid paper has better mechanical and electrical properties.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides a method for preparing aramid micro-nano particles, comprising the following steps:

[0008] S1. Dissolve a certain amount of poly(m-phenylene isophthalamide) (PMIA) in an organic solvent, heat and stir to completely dissolve it, and obtain a PMIA solution;

[0009] S2. The PMIA solution in step S1 is sucked into a syringe with a needle, and the syringe is fixed on a micro-propulsion pump of an electrostatic spray device to obtain monodisperse PMIA micro-nanoparticles by electrostatic spraying.

[0010] Preferably, in step S1, the concentration of the PMIA solution is 1 to 10 wt %;

[0011] Preferably, in step S1, the heating temperature is 50-85°C, and the stirring speed is 300-700 rpm;

[0012] Preferably, in step S1, the organic solvent is N,N'-dimethylacetamide (DMAC) containing CaCl2 or LiCl, and the mass fraction of the CaCl2 or LiCl is 2-10 wt%.

[0013] Preferably, in step S2, the syringe is a 5 mL medical syringe, and the needle is a 30-19G flat-top metal needle.

[0014] Preferably, in step S2, the parameters of the electrostatic spray method are set as follows: the flow rate of the micro-propulsion pump is 0.02-0.075 mm / s, the distance from the needle to the collector is 15 cm-33 cm, the negative voltage is -15 kV, the positive voltage is 6 kV-9 kV, the temperature of the internal environment of the electrostatic spray device is 120-160°C, and the humidity is 2-50%.

[0015] The second aspect of the present invention provides aramid micro-nano particles obtained by the above preparation method, wherein the diameter of the aramid micro-nano particles is 100 nm to 10 μm.

[0016] The third aspect of the present invention provides the use of the above-mentioned aramid micro-nanoparticles as a filler in the preparation of aramid paper.

[0017] The present invention has the following beneficial effects:

[0018] (1) The present invention uses a dispersion of poly(m-phenylene isophthalamide) (PMIA) as a raw material and prepares aramid micro-nano particles by an electrostatic spraying method. By adjusting the process parameters, aramid micro-nano particles with different particle sizes ranging from hundreds of microns to tens of nanometers can be obtained. The aramid micro-nano particles have a narrow particle size distribution and have the advantages of large output and high purity, and have important application prospects in industry.

[0019] (2) When the aramid micro-nano particles prepared by the present invention are mixed with aramid short fibers and / or fibrils, they can fill the pores between the aramid short fibers and / or fibrils. Under the action of hot pressing, the bulk thereof melts and acts as a "bridging" particle to firmly bond the adjacent aramid short fibers and / or fibrils. By increasing the fluidity of the aramid micro-nano particles during the hot pressing process, the residual pores in the aramid paper are reduced to the maximum extent, the interfacial cohesion (interfacial adhesion and cohesion) and the density of the finished paper are improved, thereby giving the paper-based material excellent mechanical strength and electrical properties. Further, by adjusting the content and size of the aramid micro-nano particles, aramid paper with high tensile strength, high breakdown voltage and high dielectric constant is obtained. In addition, the mechanical and electrical properties of the aramid fibers can be fundamentally improved, so that the obtained aramid paper can be used in high-end applications while reducing the use of chemicals.

[0020] (3) The preparation method of the present invention has the characteristics of simple preparation process, high yield, safety and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is a SEM image of the aramid micro-nano particles prepared in Example 1;

[0023] Figure 2 The surface and cross-sectional SEM images of the aramid paper prepared in Experimental Example 1;

[0024] Figure 3 The surface and cross-sectional SEM images of the aramid paper prepared in Experimental Example 2;

[0025] Figure 4 The surface and cross-section SEM images of the aramid paper prepared in Experimental Example 3. DETAILED DESCRIPTION

[0026] In the following description, for the purpose of illustration rather than limitation, specific details such as specific system structures and technologies are provided to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may also be implemented in other embodiments without these specific details.

[0027] Example 1

[0028] A method for preparing aramid micro-nano particles, the specific steps are as follows:

[0029] S1, dissolving 2 g of poly(m-phenylene isophthalamide) (PMIA) in 60 mL of a mixed solvent of N,N'-dimethylacetamide (DMAC) and 9% CaCl2, heating to 60°C, stirring at 500 rpm, and completely dissolving the mixture to obtain a PMIA solution;

[0030] S2. The obtained PMIA solution is sucked into a 5 mL syringe with a flat-top needle, and the syringe is replaced with a 30G flat-top metal needle. Then, the syringe is installed on a propulsion pump in an electrostatic spray device at an ambient temperature of 60°C, and the flow rate of the propulsion pump is set to 0.05 mm / s. The positive high voltage is connected to the metal flat-top needle. The aluminum foil used as a collector is fixed on an insulating plate and connected to a negative high voltage power supply. The distance from the flat-top needle to the collector is adjusted to 25 cm. At this time, the internal ambient temperature of the electrostatic spray device cavity is set to 120°C, and the humidity is 10%. Turn on the switch of the propulsion pump, first adjust the negative voltage to -15 kV, and then adjust the positive voltage to 7.5 kV. At this time, a Taylor cone appears on the flat-top needle. After stabilizing for a period of time, the instrument is turned off to obtain monodisperse aramid micro-nanoparticles. The product purity is 96.1% and the yield is 94%. The monodisperse aramid micro-nanoparticles obtained in this example are characterized, and a scanning electron microscope image is obtained (see Figure 1 ),Depend on Figure 1 The results show that the particle size of the aramid micro-nano particles obtained in the present invention is about 600 nm.

[0031] Example 2

[0032] A method for preparing aramid micro-nano particles, the specific steps are as follows:

[0033] S1, dissolving 5 g of poly(m-phenylene isophthalamide) (PMIA) in 60 mL of a mixed solvent of N,N'-dimethylacetamide (DMAC) and 9% CaCl2, heating to 60°C, stirring at 500 rpm, and completely dissolving the mixture to obtain a PMIA solution;

[0034] S2. The obtained PMIA solution was sucked into a 5 mL syringe with a flat-top needle, and the syringe was replaced with a 20G flat-top metal needle. Then, the syringe was installed on a propulsion pump in an electrostatic spray device at an ambient temperature of 60°C, and the flow rate of the propulsion pump was set to 0.05 mm / s. The positive high voltage was connected to the metal flat-top needle, and the aluminum foil used as a collector was fixed on an insulating plate and connected to a negative high-voltage power supply. The distance from the flat-top needle to the collector was adjusted to 25 cm. At this time, the internal environment of the electrostatic spray device cavity was set to a temperature of 120°C and a humidity of 10%. The switch of the propulsion pump was turned on, and the negative voltage was first adjusted to -15 kV, and then the positive voltage was adjusted to 7.5 kV. At this time, a Taylor cone appeared on the flat-top needle. After stabilization for a period of time, the instrument was turned off to obtain monodisperse aramid micro-nano particles with a product purity of 94.3% and a yield of 97%. The monodisperse aramid micro-nano particles obtained in this example were characterized, and the particle size was found to be about 2 μm.

[0035] Example 3

[0036] A method for preparing aramid micro-nano particles, the specific steps are as follows:

[0037] S1, dissolving 0.5 g of poly(m-phenylene isophthalamide) (PMIA) in 60 mL of a mixed solvent of N,N'-dimethylacetamide (DMAC) and 9% CaCl2, heating to 60°C, stirring at 500 rpm, and completely dissolving the mixture to obtain a PMIA solution;

[0038] S2, the PMIA solution was sucked into a 5mL syringe with a flat-top needle, the syringe was replaced with a 27G flat-top metal needle, and then the syringe was installed on a propulsion pump in an electrostatic spray device at an ambient temperature of 60°C, the flow rate of the propulsion pump was set to 0.05mm / s, the positive high voltage was connected to the metal flat-top needle, the aluminum foil as a collector was fixed on an insulating plate and connected to a negative high voltage power supply, and the distance from the flat-top needle to the collector was adjusted to 25cm. At this time, the internal environment of the electrostatic spray device cavity was set to 120°C and the humidity was 10%. The switch of the propulsion pump was turned on, and the negative voltage was first adjusted to -15kV, and then the positive voltage was adjusted to 7.5kV. At this time, a Taylor cone appeared on the flat-top needle. After stabilization for a period of time, the instrument was turned off to obtain monodisperse aramid micro-nano particles, and the product purity was 94.7% and the yield was 95.1%. The monodisperse aramid micro-nano particles obtained in this embodiment were characterized, and the particle size was about 100nm.

[0039] Example 4

[0040] A method for preparing aramid micro-nano particles, the specific steps are as follows:

[0041] S1, dissolving 0.1 g of poly(m-phenylene isophthalamide) (PMIA) in 60 mL of a mixed solvent of N,N'-dimethylacetamide (DMAC) and 9% CaCl2, heating to 60°C, stirring at 500 rpm, and completely dissolving the mixture to obtain a PMIA solution;

[0042] S2, the PMIA solution was sucked into a 5mL syringe with a flat-top needle, the syringe was replaced with a 27G flat-top metal needle, and then the syringe was installed on a propulsion pump in an electrostatic spray device at an ambient temperature of 60°C, the flow rate of the propulsion pump was set to 0.1mm / s, the positive high voltage was connected to the metal flat-top needle, the aluminum foil as a collector was fixed on an insulating plate and connected to a negative high-voltage power supply, the distance from the flat-top needle to the collector was adjusted to 25cm, and the internal environment of the electrostatic spray device cavity was set to 140°C and the humidity was 50%, the propulsion pump was turned on, the negative voltage was first adjusted to -15kV, and then the positive voltage was adjusted to 7.5kV, at this time, the flat-top needle appeared Taylor cone, and the instrument was turned off after stabilization for a period of time, and monodispersed aramid micro-nano particles were obtained, the product purity was 96.3%, and the yield was 92%. The monodispersed aramid micro-nano particles obtained in this embodiment were characterized, and the particle size was about 800nm.

[0043] Test Example 1

[0044] Aramid nanoparticles are used as fillers and mixed with micron-sized aramid short fibers and precipitated fibers, and then industrial aramid paper is prepared by an oblique-net papermaking method. The specific steps are as follows:

[0045] (1) The aramid micro-nano particles, aramid short fibers and aramid nanofibers obtained in Example 1 were placed in an aqueous solution at a mass ratio of 1:6:3, and stirred at a speed of 10,000 rpm for 5 minutes by a high-speed deflaker to obtain a mixed fiber dispersion with a concentration of 1.5‰;

[0046] (2) The obtained mixed fiber dispersion was transferred to the inside of the inclined wire paper machine, and the papermaking operation was carried out by the inclined wire paper machine, and finally placed on a roller calender for hot pressing. The hot pressing conditions of the roller calender were: temperature 180°C, pressure 12MPa, and time 18min, to obtain high-performance aramid paper. The obtained high-performance aramid paper was characterized, such as Figure 3 Shown are scanning electron microscope images of the surface and cross-section of the prepared aramid paper.

[0047] In this embodiment, the aramid paper prepared by the above steps has a thickness of 0.05 mm and a gram weight of 41.5 g / m 2, tensile strength: longitudinal 80N / cm, transverse 32N / cm, elongation: longitudinal elongation 9.5%, transverse elongation 6.1%, initial tear strength: longitudinal 12.1N, transverse 8.1N, dielectric strength 25.3kV / mm.

[0048] Test Example 2

[0049] The present invention prepares industrial aramid paper by blending micron-sized aramid short fibers, precipitated fibers and aramid micro-nano fillers and using an oblique-net papermaking method. The specific steps are as follows:

[0050] (1) The aramid micro-nano particles obtained in Example 1, the raw aramid short fibers and the aramid nanofibers were mixed in an aqueous solution at a mass ratio of 4:6, and the mixture was processed by a high-speed deflaking machine at a speed of 10,000 rpm for 5 min to obtain a mixed dispersion having an aramid concentration of 1.5‰;

[0051] (2) The fiber dispersion obtained above is transferred to the interior of an inclined wire paper machine and papermaking operation is performed on the inclined wire paper machine, and finally placed on a roller calender for hot pressing. The hot pressing conditions of the roller calender are: temperature 180°C, pressure 12 MPa, and time 18 minutes, to obtain improved high-performance aramid paper. Figure 3 are the scanning electron microscopy results of the surface and cross section of the prepared aramid paper.

[0052] Depend on Figure 3 The results show that the aramid paper obtained by mixing only aramid micro-nanoparticles and short fibers has surface and cross-sectional results similar to those of Test Example 2, and has the advantages of high paper density, good interface adhesion, few cross-sectional pores, and good surface coating.

[0053] The aramid paper prepared in this embodiment has a thickness of 0.046 mm and a gram weight of 42.0 g / m 2 , tensile strength: longitudinal 85N / cm, transverse 35N / cm, elongation: longitudinal elongation 9.9%, transverse elongation 6.5%, initial tear strength: longitudinal 13.5N, transverse 9.5N, dielectric strength 27.3kV / mm.

[0054] Test Example 3

[0055] The present invention prepares industrial aramid paper by blending micron-sized aramid short fibers and precipitated fibers and using an oblique-net papermaking method, and the specific steps are as follows:

[0056] Aramid chopped fibers and aramid nanofibers were placed in an aqueous solution at a mass ratio of 6:4, and stirred at a speed of 10000 rpm for 5 minutes by a high-speed deflaking machine to obtain a mixed fiber dispersion with a concentration of 1.5‰.

[0057] The obtained mixed fiber dispersion was transferred to the interior of the inclined wire paper machine and papermaking operation was performed through the inclined wire paper machine, and finally placed on a roller calender for hot pressing treatment. The hot pressing conditions were: temperature 180°C, pressure 12MPa, time 18min, to obtain aramid paper. Figure 4 The following are scanning electron microscope images of the surface and cross section of the prepared aramid paper. Figure 4 The results show that the aramid paper obtained in this test example has many large pores in the cross section due to the poor interface adhesion between the precipitated fibers and the aramid short fibers and the general surface coating.

[0058] The aramid paper prepared in this test example has a thickness of 0.048 mm and a gram weight of 39.5 g / m 2 , tensile strength: longitudinal 43N / cm, transverse 15N / cm, elongation: longitudinal elongation 4.1%, transverse elongation 3.1%, initial tear strength: longitudinal 8.1N, transverse 4.5N, dielectric strength 12.2kV / mm.

[0059] In summary, the performance test results of the aramid paper prepared according to the above test examples 1 to 3 are shown in the following table:

[0060]

[0061] As shown in the results of Table 1, the aramid paper filled with aramid micro-nano particles in Test Examples 1 and 2 of the present invention has been improved in terms of thermal stability and mechanical and electrical properties, and the tensile strength and thermal stability of the aramid paper with added nano-aramid micro-nano particles are higher than those of conventional aramid paper. This is because compared with traditional precipitated fibers, the three-dimensional dimensions of aramid micro-nano particles are relatively small, and they have better fluidity and fillability during the hot pressing process. Therefore, in the results of scanning electron microscopy, it is found that the residual pores in the cross section are small, the surface coating is good, and the interface adhesion is good. The final aramid paper has a higher density and better mechanical and electrical properties.

[0062] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.

Claims

1. Application of aramid micro-nano particles as fillers in aramid paper, characterized in that: The method for preparing the aramid micro-nano particles comprises the following steps: S1. Dissolve a certain amount of poly(m-phenylene isophthalamide) (PMIA) in an organic solvent, heat and stir to completely dissolve it, and obtain a PMIA solution; S2. The PMIA solution in step S1 is sucked into a syringe with a flat-top needle, and the syringe is fixed on a micro-propulsion pump of an electrostatic spray device to obtain monodisperse PMIA micro-nanoparticles by electrostatic spraying; The parameters of the electrostatic spray are set as follows: the flow rate of the micro-propulsion pump is 0.02-0.075 mm / s, the distance from the needle to the collector is 15 cm-33 cm, the negative voltage is -15 kV, the positive voltage is 6 kV-9 kV, the temperature of the internal environment of the electrostatic spray device is 120-160° C., and the humidity is 2-50%.

2. The use of the aramid micro-nano particles as a filler in aramid paper according to claim 1, characterized in that: In step S1, the concentration of the PMIA solution is 5-30 wt%.

3. The use of the aramid micro-nano particles as a filler in aramid paper according to claim 1, characterized in that: In step S1, the heating temperature is 50-85° C., and the stirring speed is 300-700 rpm.

4. The use of the aramid micro-nano particles as a filler in aramid paper according to claim 1, characterized in that: In step S1, the organic solvent is N,N'-dimethylacetamide containing CaCl2 or LiCl, and the mass fraction of CaCl2 or LiCl is 2-10wt%.

5. The use of the aramid micro-nano particles as a filler in aramid paper according to claim 1, characterized in that: In step S2, the syringe is a 5 mL medical syringe, and the needle is a flat-top metal needle of 27G to 19G.

Citation Information

Patent Citations

  • Aramid paper coated with aramid nanofibers and preparation method of aramid paper

    CN111235944A

  • Preparation method of aramid paper added with nanofibers

    CN115216991A

  • Composite nanometer filter material and its preparation method and use

    CN106540490A

  • Aramid fiber micro-nano fiber with net-shaped structure as well as preparation method and application of aramid fiber micro-nano fiber

    CN113969427A

  • Aramid fibrid and preparation method and application thereof

    CN115110171A

Cited By

  • Preparation method of aramid micro-nano particles and application of aramid micro-nano particles in aramid paper

    CN117924750A

  • Aramid fiber micro-nano particle as well as preparation method and application thereof

    CN117946423A